Effects of Fe on Catalytic Hydrogenation of Palm Oil in Aqueous Solution - Liew, Hua Wu; Mohd Ridzuan, Nordin; Zahira, Yaakob; Kong, Yong Liew; Jin, Lin Li (Springer, 2017)
Chitosan-stabilised metallic Pd (CTS-Pd) and Pt (CTS-Pt) nanoparticles were synthesised and used for the hydrogenation of palm oil. With the goal of preparing hydrogenated oil with low trans fatty acid (TFA) content under ambient conditions, Fe anion was added as the secondary metallic precursor to synthesise chitosan-stabilised bimetallic Pd–Fe (CTS-Pd–Fe) and Pt–Fe (CTS-Pt–Fe) nanoparticles. The catalytic hydrogenations with newly prepared nanoparticles were performed in aqueous solution under ambient temperature and atmospheric pressure. The addition of Fe was found to improve the catalytic activity and decrease the selectivity for TFA. Hydrogenation with CTS-Pt–Fe affords the optimal results, producing 3.8% TFA at 92.1% conversion of C18:2 and no TFA was formed until the content of C18:2 was lower than 1.7%. Based on the analyses, it can be demonstrated that the preferential conversion of C18:2 to cis C18:1 and cis C18:1 to C18:0 leads to the low formation of TFA.